Long‐term outcome of consecutive case series of congenital isolated agenesis of corpus callosum. (2nd October 2022) - Lanna, M.; Scelsa, B.; Cutillo, G.; Amendolara, M.; Doneda, C.; Balestriero, M.; Faiola, S.; Casati, D.; Spaccini, L.; Cetin, I.
ABSTRACT: Objective: To describe the long‐term outcome of children with prenatally diagnosed isolated complete agenesis of the corpus callosum (cACC). Methods: In this single‐center case series, we reviewed retrospectively the charts of fetuses referred to our fetal therapy unit from January 2004 to July 2020 for a suspected anomaly of the corpus callosum (CC). Cases with prenatally diagnosed isolated cACC were included. Fetal karyotype and comparative genomic hybridization microarray of amniotic fluid, in addition to fetal magnetic resonance imaging, were offered to all pregnant women with a diagnosis of fetal CC malformation. The surviving children were enrolled in the neurodevelopmental follow‐up program at our institution, which included postnatal magnetic resonance imaging, serial neurological examinations and neurodevelopmental evaluations with standardized tests according to age. Families living in remote areas or far from our institution were offered a structured ad‐hoc phone interview. Results: A total of 128 pregnancies with fetal CC malformation were identified (mean gestational age at diagnosis, 24.5 (range, 21–34) weeks), of which 53 cases were diagnosed prenatally with apparently isolated cACC. Of these, 12 cases underwent termination of pregnancy, one resulted in intrauterine demise at 24 weeks of gestation and 13 cases were lost to follow‐up. Of the remaining 27 children, one was excluded due to an associated chromosomal anomaly (8p21.3q11.21 mosaic duplication) diagnosed after birth, which could have been detected prenatally if the parents had consented to amniocentesis. In the 26 children included in the analysis, neurodevelopmental follow‐up was available for a median of 3 (range, 1–16) years. Three (11.5%) infants had severe neurodevelopmental impairment, two of which were diagnosed postnatally with a genetic syndrome (Mowat–Wilson syndrome and Vici syndrome) that would not have been diagnosed prenatally. Seven (26.9%) children had mild neurodevelopmental impairment and 16 (61.5%) had normal neurodevelopmental outcome. The Full‐Scale Intelligence Quotients of the three children with severe neurodevelopmental impairment were 50, 64 and 63, respectively, while that of the remaining children was in the normal range (median, 101; range, 89–119). Conclusions: In 88% of the children with cACC included in this study, neurodevelopment was not severely impaired. However, long‐term follow‐up is recommended in all cases of congenital isolated cACC to recognize subtle neurodevelopmental disorders as early as possible. © 2022 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Jiang and Li. Click here to view the Correspondence.